Publisher Correction: Liquid phase blending of metal-organic frameworks. Issue 1 (December 2018) - Longley, Louis; Collins, Sean; Zhou, Chao; Smales, Glen; Norman, Sarah; Brownbill, Nick; Ashling, Christopher; Chater, Philip; Tovey, Robert; Schönlieb, Carola-Bibiane; Headen, Thomas; Terrill, Nicholas; et al.
The original version of this Article contained an error in Figure 1b, where the blue '(ZIF-4-Zn)0.5 (ZIF-62)0.5 blend' data curve was omitted from the enthalpy response plot. This has now been corrected in both the PDF and HTML versions of the Article.